Emergency Ultra-Deep Hypothermia in Cardiac Arrest Induced by Blood Loss (Experimental Study on Nonhuman Primates) - Victor A. Reva; Anastasia R. Samakaeva; Daniil A. Shelukhin; Sergey V. Orlov; Vladimir D. Potemkin; Dmitry V. Bulgin; Galina Y. Gracheva; Alexey V. Shchegolev (Общая реаниматология, 2025)
The survival rate of critically injured individuals with severe blood loss and cardiac arrest is close to zero.Aim. To evaluate the feasibility of using emergency ultra-deep hypothermia (EUDH) in an experimental model of cardiac arrest induced by blood loss in nonhuman primates.Materials and Methods. Five male olive baboons (Papio anubis), weighing 19.8 (18.8–23.8) kg, were subjected to severe blood loss leading to cardiac arrest. After 1 minute of observation and 3 minutes of cardiopulmonary resuscitation (CPR), aortic arch cooling was initiated using extracorporeal membrane oxygenation (ECMO) with a 4°C solution to achieve a nasopharyngeal temperature of 10°C. Whole-body cooling followed until a rectal temperature of 16°C was reached. Balloon catheters were used to disconnect the upper and lower halves of the body. Once the target temperatures were reached, the ECMO circuit was turned off and an open laparotomy was performed to simulate damage control strategies. One hour after cardiac arrest, slow rewarming began at a rate of 1°C per 10 minutes to 1°C per hour, accompanied by reinfusion of previously collected blood. After return of spontaneous circulation (ROSC), sustained breathing, and tracheal extubation, the animals were transferred to a vivarium.Results. During deep hypothermia, cerebral oximetry values remained within normal limits in all animals. Sustained ROSC was recorded in 4 of 5 animals at temperatures between 22–25°C. Two animals survived to the end of the experiment but died after extubation, 44 and 19 hours after the start of the experiment. Cooling rates for survivors were 7–11 minutes compared to 23–37 minutes for non-survivors. Causes of death included systemic hypoperfusion with subsequent reperfusion syndrome as evidenced by progressive lactate elevation, elevated creatine phosphokinase levels, cerebral edema, myocardial ischemia, and transient coagulopathy.Conclusion. EUDH supports adequate cerebral perfusion during temporary circulatory arrest. Recovery of cardiac activity and, in some cases, awakening are achievable during the rewarming phase. Causes of death and possible corrective measures require further investigation.